The influence of a binary alloy of the Al-Cr system on the tribological properties of ultra-high-molecular-weight polyethylene - O.I. Popil; А.-М.V. Tomina (Проблеми трибології)
The work studied the influence of a liquid-quenched binary alloy of the Al-Cr system with a chromium content of 5 wt.% on the tribological properties of ultra-high-molecular-weight polyethylene under friction without lubrication according to the “disk-pad” scheme and with rigidly fixed abrasive particles. We established that the introduction of 5-30 wt.% this alloy leads to a decrease in the intensity of linear wear and the abrasive wear rate of ultra-high-molecular-weight polyethylene by 2.8 and 2 times, respectively. On the other hand, this can be explained by the formation of a more strained Al-based solid solution lattice, since it is known that binary quenched from the liquid state aluminum-based alloys are characterized by a high degree of microstresses due to the significant difference in the sizes of Al-Cr atoms. A composite with a filler content of 20 wt.% has the best set of functional properties. We can recommend this material for the manufacture of tribotechnical (gears, sprockets, bushings, and plain bearings) and structural (rollers, gear wheels, and bearing housings) parts for agricultural machinery and the mining industry operating under conditions of impact-abrasive or fatigue wear.